The Impact of Bad Parenting on Children’s Mental Health in Movie "MOTHER" (2020) by Tatsushi Omori: A Psychological Approach - Abdillah, Muhammad Ilham; Nugroho, Abdillah (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
The goal of this study is to look into the toxic parenting pattern used by a single parent named Akiko towards her child, Shuhei. This study will look at several types of toxic parenting as well as the psychological state of a child who has been subjected to toxic parenting treatment. This study employs a qualitative descriptive approach with informal methodologies. This study employs Hurlock's family role theory and Minderop's literary psychological theory. According to the findings of this research, Akiko plays a significant role in the family as a mother, which places Shuhei under Akiko's authority and influence. Akiko's poisonous parenting style is one that approaches dictatorial behaviour. Shuhei is put off by Akiko's authoritarian actions, which appear overly strict or overprotective. The effects of these treatments had an effect on Shuhei's psychological state.